Zasada równego traktowania kobiet i mężczyzn w zakresie dostępu do zatrudnienia oraz warunków pracy w świetle orzecznictwa Trybunału Sprawiedliwości Unii Europejskiej - Szczerba-Zawada, Aleksandra (Studia Iuridica Toruniensia, 2011)
<!--[if gte mso 9]> <![endif]--> The principle of equal treatment for men and women is the unquestionable foundation of the European Union legal order. It accompanied the process of the European integration from the very beginning, on the one hand determining its direction, on the other – being shaped by the process of European integration as its gradual development implied the successive extension of its scope of application to new areas such as access to employment and working conditions. The aim of this article is to present the way in which the Court of Justice of the European Union construed the prohibition of gender discrimination as regards the terms of employment, quite often specifying or even extending its meaning through the system of precedents. In this aim the article concentrates on the scope of application of the equal treatment principle in employment and occupation regardless of sex, accepted exceptions to it and legal consequences of the infringement of this principle. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->